Receptor-Targeted Fluorescence-Guided Surgery With Low Molecular Weight Agents - Hernandez Vargas, Servando; Lin, Christie; Tran Cao, Hop S.; Ikoma, Naruhiko; AghaAmiri, Solmaz; Ghosh, Sukhen C.; Uselmann, Adam J.; Azhdarinia, Ali (Frontiers in Oncology, 2021)
Cancer surgery remains the primary treatment option for most solid tumors and can be curative if all malignant cells are removed. Surgeons have historically relied on visual and tactile cues to maximize tumor resection, but clinical data suggest that relapse occurs partially due to incomplete cancer removal. As a result, the introduction of technologies that enhance the ability to visualize tumors in the operating room represents a pressing need. Such technologies have the potential to revolutionize the surgical standard-of-care by enabling real-time detection of surgical margins, subclinical residual disease, lymph node metastases and synchronous/metachronous tumors. Fluorescence-guided surgery (FGS) in the near-infrared (NIRF) spectrum has shown tremendous promise as an intraoperative imaging modality. An increasing number of clinical studies have demonstrated that tumor-selective FGS agents can improve the predictive value of fluorescence over non-targeted dyes. Whereas NIRF-labeled macromolecules (i.e., antibodies) spearheaded the widespread clinical translation of tumor-selective FGS drugs, peptides and small-molecules are emerging as valuable alternatives. Here, we first review the state-of-the-art of promising low molecular weight agents that are in clinical development for FGS; we then discuss the significance, application and constraints of emerging tumor-selective FGS technologies.